Your gut is still not smarter than your head : - Clancy, Kevin J. (Wiley, 2007)
In Your Gut Is Still Not Smarter Than Your Head, marketing consultants Kevin Clancy and Peter Krieg explain how to implement disciplined, accountable marketing practices that get quantifiable results. The methodologies they describe, based on state-of-the-science research and modeling, will revolutionize marketing in the same way Six Sigma revolutionized manufacturing